2021
DOI: 10.3390/healthcare10010040
|View full text |Cite
|
Sign up to set email alerts
|

Perception of E-Resources on the Learning Process among Students in the College of Health Sciences in King Saud University, Saudi Arabia, during the (COVID-19) Outbreak

Abstract: Aim: to assess the impact of e-learning through different e-resources among health sciences students. Methodology: A cross-sectional design was conducted among health science students (n = 211; 134 female and 77 male) at King Saud University, Saudi Arabia. The data was collected using a previously used structured questionnaire to assess the impact of e-resources on learning. Results: The four most frequently used e-resources were: Zoom (38%), YouTube (31%), Google applications (29%), and Blackboard (27%). More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The reduced clinical experience emerging from the transition from the face-to-face to online stmctures is of major concern to Oral Radiology. Some authors 20 have suggested a broad variety of digital resources for teaching, such as Zoom, Blackboard, and Google applications. Others 21 have suggested the implementation of online joumal clubs and case discussions to trigger student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced clinical experience emerging from the transition from the face-to-face to online stmctures is of major concern to Oral Radiology. Some authors 20 have suggested a broad variety of digital resources for teaching, such as Zoom, Blackboard, and Google applications. Others 21 have suggested the implementation of online joumal clubs and case discussions to trigger student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, some authors underline that the lack of contact affects the attitudes related to e-learning [ 48 , 49 , 50 , 51 ]. This important issue requires investment in infrastructure and teaching skills development to make students’ learning satisfactory [ 52 , 53 ]. In line with these studies, although e-learning is considered easily usable and a valid educational alternative, our data showed that students did not have a positive attitude towards these tools, especially for their use in the future.…”
Section: Discussionmentioning
confidence: 99%